Electric field dependence of ferroelectric stability in BiFeO3 thin films co-doped with Er and Mn. Issue 11 (1st August 2020) - Liu, Yun; Tan, Guoqiang; Ren, Xixi; Li, Jincheng; Xue, Mintao; Ren, Huijun; Xia, Ao; Liu, Wenlong
Abstract: Bi0.9 Er0.1 Fe1− x Mn x O3 (BEFM x O, x  = 0.00–0.03) films are synthesized by a sol–gel technique. The BEFO film exhibits a conduction mechanism based on electron tunneling. The high applied electric field causes dissociation of the defect complex, and the resulting oxygen vacancies contribute to fake polarization. Consequently, the BEFO film has poor polarization stability at high applied electric fields. Coexistence of two phases (with space groups R3c:H and R3m:R) and reduced concentrations of oxygen vacancies and Fe 2+ in BEFM x O are achieved by co-doping with Er and Mn. The presence of bulk-based conduction in the BEFM x O films then leads to ferroelectric domain switching contributing to the real polarization and to excellent ferroelectric stability. In addition, the BEFM0.02 O film shows a typical symmetrical butterfly curve, the highest remnant polarization of ~109 μC/cm 2, and the highest switching current of ~1.66 mA. It also has the smallest oxygen vacancy concentration and thus the smallest amount of defect complex, which means that there are fewer pinning effects on ferroelectric domains and therefore excellent ferroelectric stability. This excellent ferroelectric stability makes the BEFM x O films obtain good stability and reliability in the application of ferroelectric memory devices.